2020
DOI: 10.2147/ott.s243552
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA EMX2OS, Regulated by TCF12, Interacts with FUS to Regulate the Proliferation, Migration and Invasion of Prostate Cancer Cells Through the cGMP-PKG Signaling Pathway</p>

Abstract: Background LncRNA EMX2OS (EMX2 opposite strand/antisense RNA) is notably downregulated in prostate cancer (PCa) tissues and may be regarded as a potential molecular biomarker for diagnosis and prognosis. However, its exact role in regulating the development of PCa is obscure. Methods The EMX2OS expression was assessed in PCa tissues, paracancer tissues, PCa cells and normal prostate epithelial cells by qPCR. Gain- and loss-of-function experiments were performed to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…Moreover, another study implied that focal adhesion was related to tumor occurrence and metastasis (Eke and Cordes, 2015). Wang et al (2020) found that the cGMP-PKG signaling pathway also has a tight relationship with proliferation, migration, and invasion in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study implied that focal adhesion was related to tumor occurrence and metastasis (Eke and Cordes, 2015). Wang et al (2020) found that the cGMP-PKG signaling pathway also has a tight relationship with proliferation, migration, and invasion in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Protective roles of this lncRNA were also found and validated in classical papillary thyroid cancer 22 , prostate cancer 23 . The role of EMX2OS in hypoxia was also reported in myalgic encephalomyelitis/chronic fatigue syndrome by Yang et al 24 .…”
Section: Discussionmentioning
confidence: 74%
“…EMX2OS, an enhancer RNA, was upregulated in low-risk ccRCC and significantly associated with low-grade, early stage, and favorable prognosis (27). Protective roles of this lncRNA were also found and validated in classical papillary thyroid cancer (28) and prostate cancer (29). The role of EMX2OS in hypoxia was also reported in myalgic encephalomyelitis/chronic fatigue syndrome by Yang et al (30).…”
Section: Discussionmentioning
confidence: 79%